Modelling hydrodynamics of horizontal flow steel slag filters designed to upgrade phosphorus removal in small wastewater treatment plants. (15th January 2018) - Barca, Cristian; Roche, Nicolas; Troesch, Stéphane; Andrès, Yves; Chazarenc, Florent
Abstract: Steel slag filters, if well designed and operated, may upgrade phosphorus removal in small wastewater treatment plants such as stabilization ponds and constructed wetlands. The main objective of this study was to develop a systemic modelling approach to describe changes in the hydraulic performances and internal hydrodynamics of steel slag filters under real dynamic operating conditions. The experimental retention time distribution curves (RTD curves) determined from tracer experiments performed at different times during the first year of operation of two field-scale steel slag filters were analyzed through a three stage process. First, a statistical analysis of the RTD curves was performed to determine statistical parameters of the retention time distribution. Second, classical tanks in series (TIS) and plug flow with dispersion (PFD) models were used to obtain a first evaluation of the dispersion and mixing regime. Finally, a multi-flow path TIS model, based on the assumption of several flow paths with different hydraulic properties, is proposed to accurately describe the internal hydrodynamics. Overall, the results of this study indicate that higher CaO content, round shape, and larger grain size distribution of steel slag may promote plug-like flow rather than dispersion. The results of the multi-flow path TIS model suggest that the internal hydrodynamics of steel slag filters can be primarily described by two main flow paths: (i) a faster main flow path showing higher plug flow, followed by (ii) a slower secondary flow path showing higher dispersion. The results also showed that internal hydrodynamics may change over time as a consequence of physical-chemical phenomena occurring in the filter, including accumulation of precipitates, slag hydration and carbonation, and particle segregation. Highlights: Internal hydrodynamics of horizontal flow steel slag filters change over time. The multi-flow path tanks in series model describes internal flow patterns well. Plug-like flow conditions increase with decreasing water temperature. Higher CaO slag content and larger grain size distribution promote plug-like flow.